2018
DOI: 10.4194/1303-2712-v18_7_06
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Italy is the first producer of rainbow trout in Europe (EU member) and Trentino farmers represent roughly 8% of this production, but genetic information of the stocks employed is still lacking. This study aimed to estimate the genetic variability of the rainbow trout stocks farmed in Trentino and to reconstruct the related admixture history. Sixty hundred and thirty -two animals belonging to 23 different stocks were analysed using microsatellite loci. Seventeen stocks showed negative values of inbreeding coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…SSR-markers were proven to be essential in studies of the genetic structure of populations for providing management of fish stocks (Olagunju, 2019). Analysis of literature sources in recent years shows that microsatellites were predominantly used in genetic studies of rainbow trout in different countries (Barat et al, 2015;Abadía-Cardoso et al, 2016;Faccenda et al, 2018) to assess the genetic variability of stocks and evaluation of their relationships, reconstruction of the admixture history. Abadía-Cardoso et al (2016) showed the possibility of identifying the differ-ences in natural populations of Oncorhynchus mykiss Walbaum, 1792 from individuals of farmed stocks and assessing the impact on rainbow trout from natural water sources during stocking.…”
Section: Introductionmentioning
confidence: 99%
“…SSR-markers were proven to be essential in studies of the genetic structure of populations for providing management of fish stocks (Olagunju, 2019). Analysis of literature sources in recent years shows that microsatellites were predominantly used in genetic studies of rainbow trout in different countries (Barat et al, 2015;Abadía-Cardoso et al, 2016;Faccenda et al, 2018) to assess the genetic variability of stocks and evaluation of their relationships, reconstruction of the admixture history. Abadía-Cardoso et al (2016) showed the possibility of identifying the differ-ences in natural populations of Oncorhynchus mykiss Walbaum, 1792 from individuals of farmed stocks and assessing the impact on rainbow trout from natural water sources during stocking.…”
Section: Introductionmentioning
confidence: 99%